2018
DOI: 10.3928/23258160-20181101-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zeiss Cirrus and Optovue RTVue OCT Angiography Systems: A Quantitative and Qualitative Approach Examining the Three Capillary Networks in Diabetic Retinopathy

Abstract: BACKGROUND AND OBJECTIVES: Construct a method for visualizing the middle capillary plexus (MCP) using Zeiss optical coherence tomography angiography (OCTA) and compare to established segmentation methods using the Optovue system. PATIENTS AND METHODS: Twenty eyes with diabetic retinopathy were imaged. Visualization of the MCP, image artifacts, preservation of pathological changes, foveal avascular zone (FAZ) area, and vessel length density (VLD) were compared between devices. RESULTS: The authors successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…The results of this study indicate that while FAZ area could be reliably measured across all three devices, statistically significant differences were found in the VD metric for both the SCP and DCP layers, especially for the Angioplex device. Our findings regarding FAZ area is consistent with Chung et al who found no significant difference in FAZ area measurements between Angiovue and Angioplex 20. Other comparison studies involving devices not included in this study did not demonstrate consistency in FAZ area measurements across devices.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study indicate that while FAZ area could be reliably measured across all three devices, statistically significant differences were found in the VD metric for both the SCP and DCP layers, especially for the Angioplex device. Our findings regarding FAZ area is consistent with Chung et al who found no significant difference in FAZ area measurements between Angiovue and Angioplex 20. Other comparison studies involving devices not included in this study did not demonstrate consistency in FAZ area measurements across devices.…”
Section: Discussionsupporting
confidence: 90%
“…While Al-Sheikh et al revealed good repeatability for FAZ area between machines, Mihailovic et al and Corvi et al found significantly different FAZ areas across devices 11,18,19. In their study evaluating twenty eyes with diabetic retinopathy, Chung et al suggested that there was no significant difference in the VD between Angioplex and Angiovue 20. However, a study conducted by Munk et al, which imaged nineteen healthy subjects on four OCT-A machines (Angiovue, Triton, Angioplex, and Spectralis), revealed that Angioplex offers the best preservation of vessel continuity in both SCP and DCP 3.…”
Section: Discussionmentioning
confidence: 98%
“… 15 – 17 Furthermore, few studies have evaluated the ICP as a distinct plexus from either the SCP or DCP. 5 , 8 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The algorithms used to calculate vessel density in OCT-A images vary; they may accompany instruments as proprietary software, or they may be made by research groups or companies to allow for post-image processing of exported images. As a result, the ensuing vessel density measurement of the same image sets or patients differ among the various devices, algorithms, scan locations, and scanned area sizes [ 42 – 45 ]. Moreover, studies comparing a variety of OCT-A-based algorithms to detect vessel density have found no single algorithm that outperforms others in all retinal plexuses examined [ 37 ].…”
Section: Discussionmentioning
confidence: 99%